2005
DOI: 10.21236/ada433368
|View full text |Cite
|
Sign up to set email alerts
|

2004 Sexual Harassment Survey of Reserve Component Members

Abstract: Public reporting btden for the collection oftiforoation is estimated to average I hor per respotse, including the tine for reviewing instructions, searching existing data sotnces, gathering and maintaining ttte data needed, and completing atd reviewing the collection of infotaation. Send cotttents regarding this btrden estimate or any other aspect of tttis collectiont ot i nfrmation, including stggestiotts for reducing this burden, to Washington Headquarters Setvices, Directorate for Informoation Operations at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Lipari et al (2003) found that among women surveyed in 2002, 50% experienced sexist behaviors, 45% crude or offensive behaviors, 27% experienced unwanted sexual attention, and 8% experienced sexually coercive behaviors in the previous 12 months. Similar results are reported in studies of reserve component personnel and cadets and midshipmen at U.S. service academies (Lipari et al, 2005(Lipari et al, , 2006.…”
Section: Incidence and Dimensions Of Sexual Harassment Of Women In Thsupporting
confidence: 86%
See 4 more Smart Citations
“…Lipari et al (2003) found that among women surveyed in 2002, 50% experienced sexist behaviors, 45% crude or offensive behaviors, 27% experienced unwanted sexual attention, and 8% experienced sexually coercive behaviors in the previous 12 months. Similar results are reported in studies of reserve component personnel and cadets and midshipmen at U.S. service academies (Lipari et al, 2005(Lipari et al, , 2006.…”
Section: Incidence and Dimensions Of Sexual Harassment Of Women In Thsupporting
confidence: 86%
“…An illustrative example of these findings can be observed in large scale studies of U.S. military personnel (Bastian et al, 1996;Fitzgerald et al, 1999;Lipari & Lancaster, 2003;Lipari et al, 2005) that have used the Sexual Experiences Questionnaire developed for the U.S. Department of Defense (SEQ-DoD; Fitzgerald et al, 1999;Stark, Chernyshenko, Lancaster, Drasgow, & Fitzgerald, 2002). Bastian et al (1996) reported that 78% of women on active duty in the U.S. military experienced some form of sexually harassing behavior in the previous 12 months; Lipari and Lancaster (2003) reported that 24% of women on active duty in the U.S. military experienced some type of sexual harassment in the previous 12 months; Lipari et al (2005) reported that 19% of women reservists in the U.S. military experienced some type of sexual harassment in the previous 12 months. Similar results are reported in studies of military cadets and midshipmen at the U.S. military academies (Government Accounting Office, 1994Lipari et al, 2006).…”
Section: Incidence and Dimensions Of Sexual Harassment Of Women In Thmentioning
confidence: 89%
See 3 more Smart Citations